Recognition memory and divergent cognitive profiles in prodromal genetic frontotemporal dementia. (June 2021) - Barker, Megan S.; Manoochehri, Masood; Rizer, Sandra J.; Appleby, Brian S.; Brushaber, Danielle; Dev, Sheena I.; Devick, Katrina L.; Dickerson, Bradford C.; Fields, Julie A.; Foroud, Tatiana M.; Forsberg, Leah K.; Galasko, Douglas R.; et al.
Abstract: Although executive dysfunction is the characteristic cognitive marker of behavioral variant frontotemporal dementia (bvFTD), episodic memory deficits are relatively common, and may be present even during the prodromal disease phase. In a cohort of mutation carriers with mild behavioral and/or cognitive symptoms consistent with prodromal bvFTD, we aimed to investigate patterns of performance on an abbreviated list learning task, with a particular focus on recognition memory. We further aimed to characterize the cognitive prodromes associated with the three major genetic causes of frontotemporal dementia, as emerging evidence suggests there may be subtle differences in cognitive profiles among carriers of different genetic mutations. Participants included 57 carriers of a pathogenic mutation in microtubule-associated protein tau ( MAPT, N = 23), or progranulin ( GRN, N = 15), or a or a hexanucleotide repeat expansion in chromosome 9 open reading frame 72 ( C9orf72, N = 19), with mild cognitive and/or behavioral symptoms consistent with prodromal bvFTD. Familial non-carriers were included as controls ( N = 143). All participants completed a comprehensive neuropsychological examination, including an abbreviated list learning test assessing episodic memory recall and recognition. MAPT mutation carriers performed worse than non-carriers in terms of list recall, and had difficulty discriminating targets from distractors on the recognition memory task, primarily due to the endorsement of distractors as targets. MAPT mutation carriers also showed nonverbal episodic memory and semantic memory dysfunction (object naming). GRN mutation carriers were variable in performance and overall the most dysexecutive. Slowed psychomotor speed was evident in C9orf72 repeat expansion carriers. Identifying the earliest cognitive indicators of bvFTD is of critical clinical and research importance. List learning may be a sensitive cognitive marker for incipient dementia in MAPT and potentially a subset of GRN carriers. Our results highlight that distinct cognitive profiles may be evident in carriers of the three disease-causing genes during the prodromal disease stage.